2018
DOI: 10.1002/mrm.27384
|View full text |Cite
|
Sign up to set email alerts
|

Precision and accuracy of cross‐sectional area measurements used to measure coronary endothelial function with spiral MRI

Abstract: Current CEF spiral MRI with in vivo SNR allows detection of a 4-5% area change and Fourier interpolation improves precision several-fold to sub-voxel dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…However, the vessel areas were measured larger with the proposed method than either of the other two, and PDV was measured lower compared to the high‐temporal sequence. With regards to the area, it has been shown that a larger voxel size, such as in the high‐temporal sequence, in combination with Fourier interpolation (used to improve precision) leads to area measurement underestimation 13 . Therefore, the larger area compared to the high‐temporal sequence was expected.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, the vessel areas were measured larger with the proposed method than either of the other two, and PDV was measured lower compared to the high‐temporal sequence. With regards to the area, it has been shown that a larger voxel size, such as in the high‐temporal sequence, in combination with Fourier interpolation (used to improve precision) leads to area measurement underestimation 13 . Therefore, the larger area compared to the high‐temporal sequence was expected.…”
Section: Discussionmentioning
confidence: 99%
“…A semi‐automatic flow analysis software was implemented in MATLAB (Mathworks, Natick, MA, USA) that included vessel segmentation and correction for background phase and through‐plane motion. All images were Fourier‐interpolated to 0.1 mm spatial resolution for more precise segmentation 13 . First, the vessel area A v was semi‐automatically computed from three consecutive end‐diastolic frames by full‐width‐half‐maximum thresholding.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations